دور وسائل الاتصال الحديثة في التنشئة الاجتماعية - غوافرية, رشيدة; بوعالية, شهرزاد (جامعة الوادي - University of Eloued, 2021)
أصبحت وسائل الاتصال تلعب دورا مهما في عملية التنشئة الاجتماعية، حيث تقدم مواد علمية وثقافية متنوعة من خلال المسرح والسينما والإذاعة المرئية والمسموعة والصحف والمجلات المختلفة والانترنت،فسهولة استخدامها، وما تحمله من مثيرات جذابة ومؤثرات فاعلة جعلها تؤخذ مكانة مرموقة داخل لمجتمعات الإنسانية ، لدا جاءت هده المداخلة من اجل التعرف على دور وسائل الإعلام في التنشئة الاجتماعية. Abstract: The means of communication play an important role in the process of socialization, where it provides a variety of scientific and cultural materials through theater, cinema, radio and television, radio, newspapers and magazines and the Internet, the ease of use and the loads of attractive stimuli and effective influences make it take a prominent place within the societies of humanity, when it came This intervention in order to identify the role of the media in socialization .
مقال
Keywords: وسائل الاتصال - التنشئة الاجتماعية; media, socialization